Sustainability of Lobster (Panulirus argus) Fisheries in Marine Protected Areas in South-eastern Mexico - Ley, Kim (Curtin University, 2015)
Sustainability aspects are assessed in two lobster (Panulirus argus) fisheries found within Biosphere Reserves in southern Mexico. These are studied using a wide range of techniques including traditional fishery science, mark and recapture methods, population genetics and stock assessment modelling procedures of analysis. New knowledge is shed as results include evaluations of the current status of these fisheries, and discussion regarding the biology of lobsters, population dynamics and management arrangements of the existing ecolabelling schemes.